2012
DOI: 10.1016/j.bbmt.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Unrelated Donor Umbilical Cord Blood Transplantation versus Unrelated Donor Bone Marrow Transplantation in Acute Leukemia Patients

Abstract: Umbilical cord blood has emerged as an alternative stem cell source to bone marrow or peripheral blood stem cells. Umbilical cord blood transplantation (UCBT) is also potentially curative for acute leukemia. However, the effect of unrelated donor bone marrow transplantation (UBMT) and UCBT on the outcome of patients with acute leukemia has not been systematically reviewed. In the present meta-analysis, we systematically searched Cochrane Library, MEDLINE, EMBASE, and CNKI up to May 2011. Two reviewers extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
(60 reference statements)
4
19
1
Order By: Relevance
“…We decided to take year 2000 as the cut-off point for our subgroup analysis, as major transplant innovation and new technologies that allegedly improve the survival outcomes of HCT was introduced in year 2000 and thereafter. Moreover, published meta-analyses on HCT comparing Cord Blood and Unrelated donor transplant and RIC versus MAC-HCT in various hematological malignancies have included HCT performed in year 2000 and beyond [15,16].…”
Section: Os and Pfs According To The Timing Of Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to take year 2000 as the cut-off point for our subgroup analysis, as major transplant innovation and new technologies that allegedly improve the survival outcomes of HCT was introduced in year 2000 and thereafter. Moreover, published meta-analyses on HCT comparing Cord Blood and Unrelated donor transplant and RIC versus MAC-HCT in various hematological malignancies have included HCT performed in year 2000 and beyond [15,16].…”
Section: Os and Pfs According To The Timing Of Transplantationmentioning
confidence: 99%
“…No additional trials were identified from recent review articles [13,[15][16][17][18][19][20][21]. After screening, 1,278 articles were excluded on the basis of relevance, design, appropriate outcome data, and duplicate publications (Fig.…”
Section: Trial Searches/selectionmentioning
confidence: 99%
“…The incidence of primary malignancy relapse was lower than other population in our transplant centers and literatures. 36,37 A reasonable interpretation of our findings is that adoptive cells mediate graft-versus-tumor (GVT) response. It is recognized that DLI induce GVT effect.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, factors influencing outcomes following HSCT are complex and include the presence/absence of MRD prior to and immediately after transplant, the donor source, and the development of graft versus host disease both in terms of its harmful toxicity as well as its potentially beneficial graft versus leukemia effects. [73][74][75][76][77] Whether the influence of these factors is age-dependent remains to be seen. Similar to the aforementioned study from the Netherlands, there may not be a general benefit to HSCT in CR1 for all AYAs with ALL.…”
Section: P=0005)mentioning
confidence: 99%